Protected pointers in wireless sensor networks. (2017) - Dini, Gianluca; Lopriore, Lanfranco
With reference to a distributed architecture consisting of sensor nodes connected by wireless links in an arbitrary network topology, we consider a segment-oriented implementation of the single address space paradigm of memory reference. In our approach, applications consist of active entities called components, which are distributed in the network nodes. A component accesses a given segment by presenting a handle for this segment. A handle is a form of pointer protected cryptographically. Handles allow an effective implementation of communications between components, and key replacement. The number of messages generated by the execution of the communication primitives is independent of the network size. The key replacement mechanism is well suited to reliable application rekeying over an unreliable network.